Towards precision irrigation management: A review of GIS, remote sensing and emerging technologies. Issue 1 (31st December 2022) - Bwambale, Erion; Naangmenyele, Zita; Iradukunda, Parfait; Agboka, Komi Mensah; Houessou-Dossou, Eva A. Y.; Akansake, Daniel A.; Bisa, Michael E.; Hamadou, Abdoul-Aziz H.; Hakizayezu, Joseph; Onofua, Oluwaseun Elijah; Chikabvumbwa, Sylvester R.
Abstract: Irrigation is the artificial application of water to crops to supply moisture. With rising drought indices and rapid population expansion, the need for irrigation water for food production is growing. Nonetheless, irrigated agriculture is battling several issues that have resulted in poor performance, inefficient water usage, and low crop water production. Improving water use efficiency in irrigated agriculture necessitates using technology that decreases water losses, matches available supplies to demand, and tracks performance. Geographical Information Systems (GIS) and Remote Sensing (RS) allow for effectively managing water and land resources for irrigation. Current GIS and RS uses in irrigation systems are covered in this study, covering land suitability for irrigation, crop water needs, irrigation scheduling, performance evaluation, and other related applications. The future potential of GIS and RS applications for sustainable irrigation water management are highlighted. This paper offers relevant information for researchers, irrigators, and policymakers on using GIS and RS in irrigation water management and how technological improvements will change irrigation water management to enhance water usage efficiency.